A novel gelatin/carboxymethyl chitosan/nano-hydroxyapatite/β-tricalcium phosphate biomimetic nanocomposite scaffold for bone tissue engineering applications - Sun, Qiushuo; Yu, Lu; Zhang, Zhuocheng; Qian, Cheng; Fang, Hongzhe; Wang, Jintao; Wu, Peipei; Zhu, Xiaojing; Zhang, Jian; Zhong, Liangjun; He, Rui (Frontiers in Chemistry, 2022)
Hydroxyapatite (HA) and tricalcium phosphate (TCP) constitute 60% of the content of bone, and their combination has a better effect on bone tissue engineering than either single element. This study demonstrates a new degradable gelatin/carboxymethyl chitosan (CMC) bone scaffold loaded with both nano-HA and β-TCP (hereinafter referred to as HCP), and freeze drying combined with stir foaming was used to obtain highly connected macropores. Only a few studies have used these components to synthesize a four-components osteogenic scaffold. The aim of this study was to comprehensively assess the biocompatibility and osteoinductivity of the nanocomposites. Three HCP/CMC/gelatin scaffolds were made with different HCP contents: Group A (10 wt% HCP), Group B (30 wt% HCP), and Group C (50 wt% HCP) (the ratio of nano-HA and β-TCP was fixed at 3:2). The scaffolds were macroporous with a high porosity and pore connectivity, as observed by morphological analysis using scanning electron microscopy. Additionally, the pore size of Group A and B was more homogeneous than Group C. There were no significant differences in physicochemical characterization among the three groups. The Fourier transform infrared (FTIR) spectroscopy test indicated that the scaffold contained active groups, such as hydroxyl, amino, or peptide bonds, corresponding to the gelatin and CMC. The XRD results showed that the phase structure of HA and β-TCP did not change in the nanocomposite. The scaffolds had biodegradation potential and an appreciable swelling ratio as demonstrated with the in vitro test. The scaffolds were cultured in vitro with MC3T3-E1 cells, showing the osteoinduction and osteoconduction increased with the HCP content. None of the scaffolds showed cytotoxicity. However, the cell adhesion and growth on Group B were better than on Group A and Group C. Therefore, freeze drying combined with a stir foaming method may have a solid component limit. This study demonstrates a novel four-component scaffold via a simple manufacturing process. Group B (30% HCP) had the best characteristics for bone scaffold materials.